Active UAV payload based on horizontal propellers for contact inspections tasks. (1st December 2020) - González-deSantos, L.M.; Martínez-Sánchez, J.; González-Jorge, H.; Arias, P.
Highlights: Importance of Structure inspection using UAVs and NDT techniques. Development of a payload for UAV for contact inspection tasks. Improved previous designs by integrating horizontal propellers. Developed control algorithms for contact inspection tasks with UAVs. Tested Contact inspection with UAVs and an ultrasonic sensor payload. Abstract: This paper presents a novel Unmanned Aerial Vehicle (UAV) payload designed to perform semi-autonomous contact inspection tasks in vertical structures. The presented system includes on-board positioning capabilities to calculate the distance and angle between the structure and the UAV that support the navigation in the neighbourhood of the structure, considered a GPS-denied area. The collected navigation parameters are the basis to control two horizontal propellers included in the payload and aimed to push the system against the structure gently and to perform the contact. Also, the proposed system has been compared to previous designs based on UAV's pitch signal control, highlighting the advantages of the new prototype. A series of tests conducted in a controlled environment demonstrate an improved contact to the structure in terms of stability and reliability, showing a contact-bounce reduction of 54.4% compared to previous experiments.